Integrative and conjugative elements in Mycoplasmopsis bovis from Western Canadian feedlot cattle: characterization and conjugative transfer - Andres-Lasheras, Sara; Zaheer, Rahat; Ortega-Polo, Rodrigo; Schwinghamer, Timothy; Abeysekara, Sujeema; Zovoilis, Athanasios; Zaidi, Sani-e-Zehra; Jelinski, Murray; McAllister, Tim A. (Frontiers in Veterinary Science, 2026)
IntroductionBovine respiratory disease (BRD) is the most significant disease affecting North American feedlot cattle. It is a multifactorial disease influenced by bacterial and viral pathogens, as well as management and environmental factors. Mycoplasmopsis bovis is among the most pathogenic bovine mycoplasmas and is associated with chronic BRD that often fails to respond to antimicrobial therapy. Integrative and conjugative elements (ICE) facilitate horizontal gene transfer among mycoplasmas and may contribute to the spread of antimicrobial resistance in M. bovis.MethodsWe identified mycoplasma ICEs (MICE) in the genomes of sequenced M. bovis isolates from western Canadian feedlot cattle (n = 124) and in vitro mating experiments to assess conjugation.Results and DiscussionOf these isolates, 33.1% harbored the array of MICE genes required for conjugation. M. bovis isolates conjugated at frequencies of 10–7–10–8 when cultured in SP4 broth under orbital agitation. Since MICE circularization is the initial step in conjugation, the presence of circular MICE (cMICE) was used as a proxy for conjugation capability (n = 451). Interestingly, 25.7% of the isolates were cMICE-positive, with a higher prevalence observed in M. bovis isolated from dairy as compared to beef feedlot cattle. Additionally, calves classified as high-risk for BRD were more likely to harbor cMICE-positive M. bovis in both cattle types. Backgrounded dairy cattle had a higher likelihood of carrying cMICE-positive M. bovis than those originating from ranches. These findings lay the groundwork for assessing cattle source as a determinant of cMICE-positive M. bovis and for developing targeted strategies to mitigate antimicrobial resistance.